Influence of alkali metal doping on surface properties and catalytic activity/selectivity of CaO catalysts in oxidative coupling of methane - Rane, V. H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2008)
Surface properties viz. surface area, basicity/base strength distribution, and crystal phases) of alkali metal doped CaO (alkali metal/Ca = 0.1 and 0.4) catalysts and their catalytic activity/selectivity ill oxidative coupling of methane (OCM) to higher hydrocarbons at different reaction conditions (viz. temperature. 700 and 750 degrees C: CH(4)/O(2) ratio. 4.0 and 8.0 and space velocity. 5140-20550 cm(3). g(-1).h(-1)) have been investigated. The influence of catalyst calcination temperature on the activity/selectivity has also been investigated. The surface properties (viz. surface area, basicity/base strength distribution) and catalytic activity/selectivity of the alkali metal doped CaO Catalysts are strongly influenced by the alkali metal promoter and its concentration in the alkali metal doped CaO catalysts. An addition of alkali Metal promoter to CaO results in a large decrease in the surface area but a large increase in the surface basicity (strong basic sites) and the C(2+) Selectivity and yield of the catalysts in the OCM process. The activity and selectivity are strongly influenced by the catalyst calcination temperature. No direct relationship between surface basicity and catalytic activity/selectivity has been observed. Among the alkali metal doped CaO catalysts. Na-CaO (Na/Ca = 0.1. before calcination) catalyst (calcined at 750 degrees C), showed best performance (C(2+) selectivity of 68.8% with 24.7% methane conversion), whereas (lie poorest performance was shown by the Rb-Cao Catalyst in the OCM process.
Keywords: alkali metal doped CaO catalysts; basicity/base strength distribution; catalytic activity/selectivity; oxidative coupling of methane